2021
DOI: 10.1101/2021.04.15.21255549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacokinetics and safety of XAV-19, a swine glyco-humanized polyclonal anti-SARS-CoV-2 antibody, for COVID-19-related moderate pneumonia: a randomized, double-blind, placebo-controlled, phase IIa study

Abstract: Background: We assessed the pharmacokinetics and safety of XAV-19, a swine glyco-humanized polyclonal antibody against SARS-CoV-2, in COVID-19-related moderate pneumonia. In vitro, 100% neutralization activity is seen with XAV-19 concentrations above 5 microg/mL. Methods: In this phase 2a trial, adults with COVID-19-related moderate pneumonia of ≤10 days duration were randomized to infusion of XAV-19 0.5 mg/kg at day 1 and day 5 (group 1), 2 mg/kg at day 1 and day 5 (group 2), 2 mg/kg at day 1 (group 3) or pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To this end, a clinical study was conducted in human subjects for XAV-19. Specifically, the concentration vs. time and effect vs. time profiles were reported for the drug in COVID-19 patients with moderate pneumonia [1]. In this study, an intravenous dose of 2 mg/kg was deemed safe, and it showed beneficial effect.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…To this end, a clinical study was conducted in human subjects for XAV-19. Specifically, the concentration vs. time and effect vs. time profiles were reported for the drug in COVID-19 patients with moderate pneumonia [1]. In this study, an intravenous dose of 2 mg/kg was deemed safe, and it showed beneficial effect.…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, XAV-19 has a half-life of 11.2 days, which allows maintenance of effective concentrations for a few weeks. This value, estimated by Gaborit et al [1] was used to determine the elimination rate constant for XAV-19 (Table 2). Table 2 shows the other parameters used to fit the pharmacokinetic and pharmacodynamic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies investigating hIVIG for COVID-19 are ongoing. The few published studies vary substantially in their setup, such as the characteristics of the studied intervention being non-human in origin (eg, horse or swine IgG) 10 , 11 or human-derived hIVIG. 12 , 13 Studies so far have been small—ranging from 18 to 245 participants—making interpretation of their results challenging.…”
mentioning
confidence: 99%